Moving Towards Eco Cultural Tourism Village (A Case Study of Pondok Cabe Village) - Kurniawati, Rina (Graduate School, Universitas Brawijaya, 2015)
This study identifies some eco-cultural tourism attraction potentials that exist in PondokCabeUdik Village Tangerang Selatan Indonesia. In addition, it investigates local people's opinion on tourism development. The objective is to provide a preliminary overview of eco-tourism development. This study is a descriptive study that uses three types of instrument in data collection method, including questionnaire, interview and field observation. The data is then analyzed using SWOT analysis. The result indicated that natural potential include farming, lake and fish pond, and chicken hatchery. Cultural potentials include cultural diversity that depicted in praying houses and culinary. 194 respondents involved are the locals. The result showed thatthere is positive view from the local community on the availability of tourism potentials and development in the future. It is proposed that environmental awareness, education, ecotourism development, and consensus buildingare needed to implement eco cultural tourism concept. Keywords: Tourism, Eco-Cultural, Village, Planning and Development